Professional Development Through Web-Based Training In Indonesia - Nabila Ghassani; Budy Sugandi (CV. Syntax Corporation Indonesia, 2023)
Professional teachers play an important role in the quality of education. Efforts to develop teacher professionalism through web-based training will be a solution for teachers in their career and professional development. Web-based TPD can be a great innovation in improving teachers' skills using technology through computers and Internet networks. Some research revealed that online learning on TPD influences on improving teacher performance. This study aimed to examine and discuss the web-based professional development in Indonesia context. Moreover, the data on this paper were obtained by literature review based on internet or printed sources. This study found that teachers can improve their ICT skills and be able to carry out professional development without leave their learning activities in the classroom through web-based training. This training activity can be easily carried out by teachers anytime and anywhere, as well as reduce the TPD activities costs